2008
DOI: 10.4025/actasciagron.v30i2.1739
|View full text |Cite
|
Sign up to set email alerts
|

Fontes e doses de zinco no feijoeiro cultivado em diferentes épocas de semeadura

Abstract: Este trabalho teve por objetivo avaliar, em diferentes épocas de cultivo a produção do feijoeiro, submetido à aplicação foliar de fontes e doses de zinco. Foi utilizado o delineamento de blocos casualizados, em esquema fatorial 3 x 2 x 5, com quatro repetições. Os tratamentos envolveram a combinação de três safras de cultivo (inverno, águas e seca), duas fontes de zinco (sulfato e cloreto de zinco) e cinco doses de zinco (0, 100, 200, 400 e 800 g ha -1 ), aplicadas via foliar, aos 25 e 35 dias após emergência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
7
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 2 publications
(3 reference statements)
5
7
0
7
Order By: Relevance
“…Pérola, que chegou a 1.795 kg ha -1 . Por outro lado, Teixeira et al (2008) verificaram, avaliando fontes (sulfato e cloreto de zinco) e doses de zinco (0, 100, 200, 400 e 800 g ha -1 ) que não houve aumento de produtividade do feijoeiro cv. Pérola à adubação com zinco via foliar em um solo com 2,1 mg kg -1 de zinco (Mehlich-1).…”
Section: Introductionunclassified
“…Pérola, que chegou a 1.795 kg ha -1 . Por outro lado, Teixeira et al (2008) verificaram, avaliando fontes (sulfato e cloreto de zinco) e doses de zinco (0, 100, 200, 400 e 800 g ha -1 ) que não houve aumento de produtividade do feijoeiro cv. Pérola à adubação com zinco via foliar em um solo com 2,1 mg kg -1 de zinco (Mehlich-1).…”
Section: Introductionunclassified
“…These results are consistent with those observed by Boaretto, Muraoka & Buoratto (2003) for the coffee crop. However, Teixeira et al (2008) found no significant difference in ZnC_L of common beans due to fertilizations with Zn chloride or sulfate.…”
mentioning
confidence: 62%
“…For cocoa, the most used Zn fertilizer for foliar fertilization is ZnSO 4 (Malavolta, 1987;Chepote et al, 2013), but studies with other crops have demonstrated (Boaretto, Muraoka & Buoratto, 2003) or not (Teixeira, Borém, Silva, & Kikuti, 2008) higher efficiency of Zn absorption when the inorganic source is ZnCl 2 ; other studies also indicate that the efficiency of Zn absorption by the leaves increases when KCl is added to the ZnSO 4 solution (Coutinho Neto et al, 2010).…”
mentioning
confidence: 99%
“…Comparing with the zero rate, the application of 1,200 g ha -1 of Zn increased ZnCG by 35%. We did not use Zn rates higher than 1,200 g ha -1 to prevent a possible leaf scorch that would be caused by the Zn solution because the highest rate of ZnF tested for correction of Zn deficiency in common bean is 800 g ha -1 (Teixeira et al, 2008). The highest ZnCG achieved in this greenhouse experiment was below the range of 53.2 to 81.2 mg kg -1 of Zn obtained by Ram et al (2016) in field experiments in Brazil, probably indicating that Zn available to plants in the present study was low.…”
Section: Resultsmentioning
confidence: 99%